Fist of the North Star. Volume 6 - Buronson, 1947- (Viz signature., 2022)
"In a postapocalyptic world, humanity has risen from the ashes of all-out nuclear war to a nightmare of endless suffering. It is a time of chaos. Warlords and gangs of savage marauders rule the broken ruins of civilization, terrorizing and enslaving the survivors. Life has become a brutal struggle for existence and death the only release. Freed from his captivity in Cassandra, Toki reveals the secret of the prison to Kenshiro. The City of Wailing Demons was established by Raoh in order to gather and confine martial artists to steal their secrets. But Raoh is not just another wasteland warlord--he is none other than Kenoh, brother of Kenshiro and Toki, who once contended for the title of successor to Hokuto Shinken! It's not long before Toki and Kenoh cross paths again and continue a deadly struggle that started long ago..."--Page [4] of cover.